Manto de invisibilidad en microondas - Septién, E.; Aboites, V. (Revista Mexicana de Física, 2012)
We present experimental results of an invisibility cloak operating in the microwave range at a 10.525 GHz frequency. The theoretical analysis is based on a conformal mapping. The experimental results were obtained from the construction of a resonant metamaterial with copper rings. A good agreement is found between both results.